2004
DOI: 10.1016/j.socscimed.2003.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Social inequality and depressive disorders in Bahia, Brazil: interactions of gender, ethnicity, and social class

Abstract: We conducted a study of the association between gender, race/ethnicity, and social class and prevalence of depressive disorders in an urban sample (N = 2302) in Bahia, Brazil. Individual mental health status was assessed by the PSAD/QMPA scale. Family SES and head of household's schooling and occupation were taken as components for a 4-level social class scale. Race/ethnicity (white, moreno, mulatto, black) was assessed with a combination of self-designation and a system of racial classification. The overall 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
1
36

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(143 citation statements)
references
References 59 publications
9
90
1
36
Order By: Relevance
“…30,35,47 Six national studies were included. [23][24][25][26][27][28][29][30] Nine studies were conducted in the Southeast region, 22,[31][32][33][43][44][45][50][51][52][53][54][55][56][57][58][59][60][61][62][63] eight in the South region, [31][32][33][34][35][36][37][38][39][40][41][42]46 two in the Northeast region [47][48][49] and one in the Mid-West region of Brazil. [31][32][33] Eight studies were conducted i...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,35,47 Six national studies were included. [23][24][25][26][27][28][29][30] Nine studies were conducted in the Southeast region, 22,[31][32][33][43][44][45][50][51][52][53][54][55][56][57][58][59][60][61][62][63] eight in the South region, [31][32][33][34][35][36][37][38][39][40][41][42]46 two in the Northeast region [47][48][49] and one in the Mid-West region of Brazil. [31][32][33] Eight studies were conducted i...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…35,47 Ten studies did not report participant losses. [23][24][25][26][27][28]30,35,45,48,49,53,62,63 To screen for the prevalence of depressive symptoms, nine studies considered self-reported depression, [23][24][25][26][27][28]30,34,46,47,53 and 11 used the following tools: 1) Adult Psychiatric Morbidity Questionnaire (Questioná rio de Morbidade Psiquiá trica de Adultos, QMPA) [31][32][33]48,49 ; 2) Beck Depression Inventory (BDI) 35,62,63 ; 3) Center for Epidemiologic Studies Depression Scale (CES-D) 29 ; 4) Composite International Diagnostic Interview ShortForm (CIDI SF) 54 ; 5) Edinburgh Postnatal Depression Scale (EPDS) 42 ; 6) Patient Health Questionnaire (PHQ-9) 40 ; and 7) Primary Care Evaluation of Mental Disorders (PRIME-MD). 45 The seven studies that screened for major depressive disorder used the following tools: the Composite International Diagnostic Interview (CIDI), 22,43,44,[50]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…To use an example from the health sciences, synergic effects of risk factors, produced by interaction processes, may be taken generally as sources of emergence in epidemiological systems. [6][7][8][9][10][11]31,70 In a study of gender, social class and race/ethnicity on prevalence of depressive disorders, 14 gender followed a pattern, confi rmed in different studies worldwide: women´s risk for depression is twice as high as men´s. Social class and race/ethnicity alone yielded low-risk estimates.…”
Section: Epistemological Backgroundmentioning
confidence: 99%
“…54 For the past 15 years, colleagues and I have developed a conceptual framework for modeling health in the light of complexity approaches. [2][3][4][5][6][7][8][9][10][11][12][13][14][15]33 Results from this line of theoretical research allowed preliminary proposals of a Theory of Modes of Health 8 and the concept of Health-Disease-Care Integrals. 6 This paper is the fi rst of a series of essays intended to advance, revise, correct and abridge updated versions of such proposals, as well as to assess feasibility and possibilities for the integration/convergence/fusion of these approaches into a unifi ed theory of health-illness-sickness.…”
Section: Introductionmentioning
confidence: 99%
“…Em estudo sobre prevalência de transtornos depressivos durante um ano na cidade de Salvador (BA), foi demonstrado que o menor nível educacional estava mais fortemente relacionado à presença de transtornos depressivos em mulheres que em homens (Almeida-Filho et al, 2004), em consonância com outros estudos conduzidos no Brasil (Ludermir e Lewis, 2001; Lima et al, 1998).…”
Section: Aspectos Psicossociaisunclassified